PERSYARATAN CALON ANGGOTA DEWAN DIKAITKAN DENGAN UPAYA MENINGKATKAN KINERJA FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT - Isharyanto, Isharyanto; Rosita, Dian (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
The Constitution of Republic of Indonesia 1945 has not explicitly regulated the requirements to become a member of House of Representatives. The requirements of prospective members of the House of Representatives as contained in Article 51 of Law Number 8 of 2012 has not fully impactedto the improvement of the legislative function of Parliament. In addition, another problems related to the main function of Parliament as a legislator is about how well the quality of act by Indonesian Parliament. Need a restructuring of internal and external factors relating to the poor performance of legislative function by the House of Representatives. So that the performance of legislative function by the House of Representatives can be implemented better in the future